Weed population dynamics and control in cultivated rice under different water regimes in the KADA region in Kelantan, Malaysia - Abdullah, Mohd Razif (2018)
This study comprised of three sets of experiment. The weed composition surveys were conducted at rice fields in Kota Bharu, Bachok, and Pasir Puteh in Kemubu Agriculture and Development Authority (KADA) region. The field experiments on weed and rice competition under different biological and ecological conditions and the effects on rice yield were conducted at a farmer’s field in Kampung Tunjong, Kota Bharu, Kelantan. The third experiment on herbicides efficacy was carried out in containers in an open area at the Pertubuhan Peladang Kawasan (PPK) Nilam Puri, Kota Bharu, Kelantan. The objectives of the research were: a) to identify weeds composition and distribution under reduced water conditions in the KADA rice fields; b) to quantify weed growth response and population dynamics, as well as rice growth and yield to different water conditions and planting methods in KADA rice field; and c) to evaluate herbicides performance and efficacy under different water conditions. In the weed survey, we identified a total of 30 weed species from 14 different families, comprising of 22 annuals and 8 perennials (6 grasses, 6 sedges, and 18 broadleaved weeds). Based on the relative abundance and ranking of the weeds in the surveyed rice fields, Fimbristylis miliacea (84.20%), Leptochloa chinensis (41.60%), Scirpus grossus (30.13%), Ischaemum rugosum (23.64%), and Echinochloa colona (20.41%) were the most prevalent and abundant species in the Off Season 2014 while Echinochloa crus-galli (62.84%), Leptochloa chinensis (37.25%), Limnocharis flava (25.12%), Fimbristylis miliacea (22.26%), and Ludwigia hyssopifolia (22.23%) highly dominated the rice fields in the Main Season 2014/2015. The survey also found that ‘padi angin’ or weedy rice occurred in the surveyed areas with 40% frequency in both planting seasons. Results from the field experiments indicated that under the two planting methods, continuous flooded at 5 cm depth (W1), continuous flooded at 2 cm depth (W2), and flooded at 5 cm depth until 45 DAS, followed by saturated (W3) exhibited an effective suppression of weeds. Plots treated W1 significantly suppressed weed population to approximately 33 – 47% and reduced weed biomass to 51 – 59% as compared to the highest in W5 in both planting season. More weed problems generally occurred in continuous saturated (W4) and field capacity (W5) conditions. However, planting method evidently exhibited stronger effect on weed suppression since transplanted plots showed significantly higher degree of weed suppression under all water regime treatments over the direct seeded plots (34 – 43%). Under both direct seeding and transplanting plots, aquatic weeds, mostly Monochoria vaginalis and Limnocharis flava were the most dominant weeds in most of the water regime treatments. Those two weed species were highly dominant during W1, W2, and W3 in Off Season 2015, outnumbering other weeds under all water regime treatments in Main Season 2015/2016, thus making the control of these weeds very important. The sedges, namely Scirpus grossus and Fimbristylis miliacea, and grasses, comprised of Leptochloa chinensis and Echinochloa crus-galli were also highly dominant in W4 and W5; therefore, the program of monitoring and control of the distribution of these weed species should be given due attention in KADA rice fields. High rice yield was achieved through the implementation of continuous flooding conditions (W1 and W2). However, high rice production was also observed in W3 (flooded at 5 cm depth until 45 DAS, followed by saturated), indicating that this water-saving regime could play an important role for rice cultivation under limited water condition. The rice production in transplanted plot was in 65.8% higher than in direct seeded plot. The percentages of reduction from the highest rice yield in W1 to lowest in W5 were 63.4%. During the herbicide pot-trial evaluation, twelve weed species were found growing across all water regime treatments. In both seasons, Monochoria vaginalis and Echinochloa crus-galli were the most dominant weed species, followed by Leptochloa chinensis, Fimbristylis milliacea, Ludwigia hyssopifolia, Limnocharis flava, Cyperus iria, and Scirpus grossus. Five of the eight treatments over the two cropping seasons showed better weed control efficiency (57 – 100%), increased grain yields (30 – 108%), and higher net benefits from the economic analysis (77 – 133%) as compared to the manual weeding treatment. Due the variation of the dominant weed infestation between water regimes, the potential treatments were pretilachor followed by bentazon/MCPA (T3) and pyrazosulfuron followed by bentazon/MCPA (T6) in flooded treatments (W1 and W2). Meanwhile, pretilachor+pyribenzoxim followed by bentazon/MCPA (T4) and bispyribac-sodium followed by bentazon/MCPA (T5) were the best weed control treatments under saturated condition (W3). For field capacity (W4), bispyribac-sodium followed bentazon/MCPA (T5) and thiobencarb+propanil followed by bentazon/MCPA (T8) showed promising results, encouraging the implementation as the possible alternative for effective and economic weed control in rice fields under dry condition.